Meaningful citizen engagement in the IDP and budgeting processes as a means to improve municipal service delivery - Ndima, Zenzo Michael (My University, 2017)
Since the inception of the democratic era in South Africa, citizen engagement has been a contentious issue for the local government sphere. In hardly a decade of democracy, cracks began to manifest on the newly-ushered system of public participation in the country, which saw communities embarking on various acts of protests around the country. Sadly, the ugly actions of dissatisfaction by the citizenry have been the order of the day since the early days of democracy, and some have been labelled it ‘a cry for attention by the disgruntled citizens’. As evidence of the disconnection in the local discourse, the aforesaid factor was regarded as a starting point in this research. As such, numbers of, and various reasons for the violent protests were examined thoroughly to establish the truth behind same. Public conversations and discussions, albeit informal, were held wherever possible, and all these pointed to the crisis of democracy in the local government. The research explored the notion of meaningful citizen engagement as a panacea for alleviating service delivery backlogs in the local government. To avoid challenges of the cause-effect scenario in analysing the processes, measurements of meaningful citizen engagement in the local government, named ‘condition’, were developed in this research. Focusing on five different categories of municipalities, fifteen officials and ten councillors were interviewed using in-depth, semi-structured interviews. Further to that, two focus group discussions were held with ten community members and eight ward committee members each, using unstructured interview questions as focal themes. Apart from the interviews, four non-participant observations (IDP/Budget meetings) were conducted in order to get a sense of the current engagement processes. Furthermore, various public documents, both internal and external of the organisations, were analysed and utilised as part of the literature review. Data from the above sets of sources were explored and analysed using the basic interpretive qualitative design and phenomenological methods to make meaning of same. The research findings suggested that current mechanisms of engagement lacked depth, and are limited in terms of opening meaningful engagement spaces for the citizens. These findings pointed to the dire need to move away from the normal, passive public participation towards the engaging, deliberative notions wherein the citizens would have opportunities to influence the final outcomes of planning and budgeting.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg; in fulfilment of the requirements for the degree of Doctor of Philosophy in Public and Development Management 6 April 2017
Keywords: Local government--South Africa--Citizen participation; Civil service--South Africa--Management; Communication in public administration--South Africa